Hybrid 'superswarm' leads to rapid divergence and establishment of populations during a biological invasion. Issue 21 (21st October 2015) - Roy, Denis; Lucek, Kay; Walter, Ryan P.; Seehausen, Ole
Abstract: Understanding the genetic background of invading species can be crucial information clarifying why they become invasive. Intraspecific genetic admixture among lineages separated in the native ranges may promote the rate and extent of an invasion by substantially increasing standing genetic variation. Here, we examined the genetic relationships among threespine stickleback that recently colonized Switzerland. This invasion results from several distinct genetic lineages that colonized multiple locations and have since undergone range expansions, where they coexist and admix in parts of their range. Using 17 microsatellites genotyped for 634 individuals collected from 17 Swiss and two non‐Swiss European sites, we reconstruct the invasion of stickleback and investigate the potential and extent of admixture and hybridization among the colonizing lineages from a population genetic perspective. Specifically, we test for an increase in standing genetic variation in populations where multiple lineages coexist. We find strong evidence of massive hybridization early on, followed by what appears to be recent increased genetic isolation and the formation of several new genetically distinguishable populations, consistent with a hybrid 'superswarm'. This massive hybridization and population formation event(s) occurred over approximately 140 years and likely fuelled the successful invasion of a diverse range of habitats. The implications are that multiple colonizations coupled with hybridization can lead to the formation of new stable genetic populations potentially kick‐starting speciation and adaptive radiation over a very short timescale.